Rules and Laws for Civil Actions - Elias, Stella Burch; Muller, Derek T.; Rantanen, Jason (Open textbook library., 2022)
Rules and Laws for Civil Actions is an open-access resource for law students containing the U.S. Constitution, Federal Rules of Civil Procedure, Federal Rules of Evidence, Federal Rules of Appellate Procedure, and selected federal and state statutes. The book was created by a team of faculty members at the University of Iowa College of Law to supplement the study of Civil Procedure, Evidence, Constitutional Law, and other law school courses. In addition to containing the official text, each legal source found in Rules and Laws for Civil Actions is accompanied by an introductory section written by an Iowa Law professor explaining its significance and background.